Method for preparing coating on titanium alloy by blue laser nitriding in situ and application thereof
Patent Information
- Application Number
- CN202611261935.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]传统的钛合金表面强化技术,如等离子体渗氮温度高、变形大,保温时间长,效率偏低;物理气相沉积(PVD)涂层为非冶金结合,结合力一般、厚度薄,承载能力有限;热喷涂结合强度一般,涂层易含孔隙,鉴于上述缺陷,提出了一种钛合金蓝光激光原位氮化制备涂层的方法及其应用
[0017]本发明中利用高能激光束,在氮气环境中对金属表面进行快速加热与冷却,生成氮化物强化层;通过改变激光功率来决定输入到材料表面的总能量,功率越高,熔池温度越高、存在时间越长,为氮原子的溶解和扩散提供了更强的驱动力,从而形成更厚的氮化层和更多的TiN硬质相的生成;通过改变激光束扫描速度来控制激光束与材料的相互作用时间和熔池的冷却速度,速度越低,作用时间越长,熔池寿命延长,热输入增加,为氮原子的扩散提供了更充裕的时间,从而形成更厚的氮化层和更多的TiN硬质相的生成;通过改变氮气流量来控制参与反应的氮源供给量,流量增大,熔池中的氮浓度升高,氮浓度梯度增大,为扩散提供更充分的物质基础,从而获得更厚的氮化层。
Smart Images

Figure CN122879700A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of titanium alloy chemical heat treatment technology, specifically to a method for preparing coatings by in-situ blue laser nitriding of titanium alloys and its application. Background Technology
[0002] Titanium and titanium alloys, due to their superior comprehensive properties such as high specific strength, excellent corrosion resistance, and outstanding biocompatibility, are widely used in aerospace, marine engineering, sports equipment, and biomedicine. However, the widespread application of titanium alloys in harsh working conditions is severely limited by their inherent surface defects, such as low hardness, poor wear resistance, and limited oxidation resistance. These surface-related limitations significantly reduce the service life and reliability of titanium alloys under high-speed, heavy-load, and severe friction conditions. Therefore, researching effective surface strengthening techniques to improve the surface properties of titanium alloys has become a key research focus for meeting the demanding requirements of titanium alloy applications.
[0003] Traditional titanium alloy surface strengthening technologies, such as plasma nitriding, have high temperatures, large deformations, long holding times, and low efficiency; physical vapor deposition (PVD) coatings are non-metallurgical bonds with generally weak adhesion, thin thickness, and limited load-bearing capacity; thermal spraying has generally weak bonding strength and the coating is prone to porosity. In view of the above defects, a method for preparing coatings by in-situ blue laser nitriding of titanium alloys and its application are proposed. Summary of the Invention
[0004] Addressing the technical bottlenecks of traditional surface strengthening techniques for titanium alloys, such as shallow hardened layers and low processing efficiency, this invention aims to provide a method for preparing coatings by in-situ blue laser nitriding of titanium alloys, which synergistically and significantly improves the surface properties of titanium alloys. By introducing high-purity nitrogen as a protective gas for the processing head, in-situ nitriding is achieved during the laser cladding process. This not only gives the titanium alloy a surface hardness far superior to that of traditional titanium alloy surface strengthening techniques, thereby significantly improving its comprehensive mechanical properties and wear resistance to meet more demanding working conditions, but more importantly, compared with traditional plasma nitriding, this invention simultaneously achieves a significant increase in nitriding efficiency, improving quality while also considering economic benefits.
[0005] To achieve the above objectives, this invention discloses a method for preparing a coating by in-situ blue laser nitriding of titanium alloys, comprising the following steps:
[0006] S1, Substrate pretreatment: Polish the titanium alloy substrate surface to a mirror finish with sandpaper, and clean it with alcohol and pure water for later use.
[0007] S2, Laser in-situ nitriding: The titanium alloy matrix obtained in step S1 is placed in the laser equipment (RC-LDM400), the laser type is selected, high-purity nitrogen gas is delivered through the coaxial protector nozzle of the processing head, and the laser power and laser beam scanning speed are adjusted at the same time to perform laser in-situ nitriding treatment.
[0008] Preferably, the base titanium alloy in step S1 is one of TC4, TA2, and TB6.
[0009] Preferably, the laser power in step S2 is 250-300 W.
[0010] Preferably, the scanning speed of the laser beam in step S2 is 6 to 10 mm / s.
[0011] Preferably, the flow rate of high-purity nitrogen in step S2 is 15-25 L / min.
[0012] Preferably, the laser in step S2 is a blue laser.
[0013] Preferably, the working environment in step S2 is an atmospheric environment.
[0014] The present invention also discloses a coating prepared by laser in-situ nitriding of titanium alloy.
[0015] This invention also discloses the application of a coating prepared by a method of in-situ laser nitriding of titanium alloys in the fields of aerospace, marine engineering and biomedicine.
[0016] The present invention also discloses the coating obtained by in-situ nitriding of the titanium alloy with blue light laser.
[0017] This invention utilizes a high-energy laser beam to rapidly heat and cool a metal surface in a nitrogen atmosphere, generating a nitride-reinforced layer. The total energy input to the material surface is determined by varying the laser power; higher power results in a higher molten pool temperature and a longer duration, providing a stronger driving force for the dissolution and diffusion of nitrogen atoms, thus forming a thicker nitride layer and generating more TiN hard phase. The interaction time between the laser beam and the material, as well as the cooling rate of the molten pool, are controlled by varying the laser beam scanning speed; a lower speed results in a longer interaction time, extending the molten pool lifetime and increasing heat input, providing more ample time for nitrogen atom diffusion, leading to a thicker nitride layer and generating more TiN hard phase. Finally, the nitrogen flow rate is adjusted to control the nitrogen source supply for the reaction; a higher flow rate increases the nitrogen concentration in the molten pool, widening the nitrogen concentration gradient and providing a more sufficient material basis for diffusion, resulting in a thicker nitride layer.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention utilizes the high absorption rate of blue laser on titanium alloys to generate TiN reinforcing phase in situ in the molten pool. By controlling the laser power, laser beam scanning speed and nitrogen flow rate, a strengthening coating is formed in situ. Compared with traditional nitriding and infrared laser nitriding, it helps to improve the mechanical, friction and wear and fatigue properties of titanium alloys. Attached Figure Description
[0019] Figure 1 The macroscopic morphological results are for Examples 1 and 4 and Comparative Examples 1 and 2;
[0020] Figure 2 The macroscopic morphological results are for Examples 1, 5, 6 and Comparative Example 3;
[0021] Figure 3 The macroscopic morphology results are for Examples 1, 7, 8 and Comparative Examples 5, 6;
[0022] Figure 4 The results are the Vickers hardness test results for the cross sections of Examples 1, 2, and 3.
[0023] Figure 5 The results of the Vickers hardness test on the cross sections of Examples 1, 4 and Comparative Example 1 are shown.
[0024] Figure 6 The results of the Vickers hardness test on the cross sections of Examples 1, 5, 6 and Comparative Example 4 are shown.
[0025] Figure 7 The results of the Vickers hardness test on the cross sections of Examples 1, 7, 8 and Comparative Example 5 are shown.
[0026] Figure 8 The results of the Vickers hardness test on the cross sections of Examples 1 and 4 and Comparative Examples 7 and 8 are shown.
[0027] Figure 9 The test results are for the cross-sectional nitride layer thickness OM of Examples 1, 2, and 3;
[0028] Figure 10 The test results are for the cross-sectional nitride layer thickness OM of Examples 1, 4 and Comparative Example 1;
[0029] Figure 11 The test results show the cross-sectional nitride layer thickness OM of Examples 1, 5, 6 and Comparative Example 4;
[0030] Figure 12 The test results show the cross-sectional nitride layer thickness OM of Examples 1, 7, 8 and Comparative Example 5;
[0031] Figure 13 The test results of the cross-sectional nitride layer thickness OM in Examples 1, 4, and Comparative Examples 7 and 8 are as follows;
[0032] Figure 14 The results of nanoindentation tests for Examples 1, 2, and 3 are shown.
[0033] Figure 15 The results of nanoindentation tests are for Examples 1, 4 and Comparative Example 1;
[0034] Figure 16 The nanoindentation test results are for Examples 1, 5, 6 and Comparative Example 4;
[0035] Figure 17 The results of nanoindentation tests are for Examples 1, 7, 8 and Comparative Example 5;
[0036] Figure 18 The results of nanoindentation tests are for Examples 1 and 4 and Comparative Examples 7 and 8;
[0037] Figure 19 The XRD test results are for Examples 1, 5, 6 and Comparative Example 4. Detailed Implementation
[0038] The above-mentioned and other technical features and advantages of the present invention will be described in more detail below with reference to the accompanying drawings.
[0039] Example 1:
[0040] In Example 1, a TC4 substrate was used, along with a 300W blue laser power, a laser beam scanning speed of 6mm / s, and a nitrogen flow rate of 20L / min, denoted as 300-6-N2O. The specific preparation method is as follows:
[0041] The TC4 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A blue laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 300W and the laser beam scanning speed at 6mm / s, while the nitrogen flow rate was controlled at 20L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0042] Example 2:
[0043] In Example 2, a TA2 matrix was used, with a blue laser power of 300W, a laser beam scanning speed of 6mm / s, and a nitrogen flow rate of 20L / min, denoted as TA-300-6-N2O. The specific preparation method is as follows:
[0044] The TA2 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A blue laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 300W and the laser beam scanning speed at 6mm / s, while the nitrogen flow rate was controlled at 20L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0045] Example 3:
[0046] In Example 3, a TB6 substrate was used, along with a 300W blue laser power, a laser beam scanning speed of 6mm / s, and a nitrogen flow rate of 20L / min, denoted as TB-300-6-N2O. The specific preparation method is as follows:
[0047] The surface of TB6 was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A blue laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 300W and the laser beam scanning speed at 6mm / s, while the nitrogen flow rate was controlled at 20L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0048] Example 4:
[0049] Example 4 uses a TC4 substrate, a 250W blue laser with a scanning speed of 6mm / s, and a nitrogen flow rate of 20L / min, denoted as 250-6-N2O. The specific preparation method is as follows:
[0050] The TC4 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A blue laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 250W and the laser beam scanning speed at 6mm / s, while the nitrogen flow rate was controlled at 20L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0051] Example 5:
[0052] Example 5 uses a TC4 substrate, a 300W blue laser with a scanning speed of 8mm / s, and a nitrogen flow rate of 20L / min, denoted as 300-8-N2O. The specific preparation method is as follows:
[0053] The TC4 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A blue laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 300W and the laser beam scanning speed at 8mm / s, while the nitrogen flow rate was controlled at 20L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0054] Example 6:
[0055] In Example 6, a TC4 substrate was used, along with a 300W blue laser power, a laser beam scanning speed of 10mm / s, and a nitrogen flow rate of 20L / min, denoted as 300-10-N2O. The specific preparation method is as follows:
[0056] The TC4 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A blue laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 300W and the laser beam scanning speed at 10mm / s, while the nitrogen flow rate was controlled at 20L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0057] Example 7:
[0058] In Example 7, a TC4 substrate was used with a blue laser power of 300W, a laser beam scanning speed of 6mm / s, and a nitrogen flow rate of 15L / min, denoted as 300-6-N15. The specific preparation method is as follows:
[0059] The TC4 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A blue laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 300W and the laser beam scanning speed at 6mm / s, while the nitrogen flow rate was controlled at 15L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0060] Example 8:
[0061] This Example 8 uses a TC4 substrate, a 300W blue laser with a scanning speed of 6mm / s, and a nitrogen flow rate of 25L / min, denoted as 300-6-N25. The specific preparation method is as follows:
[0062] The TC4 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding treatment. A blue laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 300W and the laser beam scanning speed at 6mm / s, while the nitrogen flow rate was controlled at 25L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0063] Comparative Example 1:
[0064] Comparative Example 1 uses a TC4 substrate, a 220W blue laser with a scanning speed of 6mm / s, and a nitrogen flow rate of 20L / min, denoted as 220-6-N2O. The specific preparation method is as follows:
[0065] The TC4 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A blue laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 220W and the laser beam scanning speed at 6mm / s, while the nitrogen flow rate was controlled at 20L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0066] Comparative Example 2:
[0067] Comparative Example 2 uses a TC4 substrate, a 320W blue laser with a scanning speed of 6mm / s, and a nitrogen flow rate of 20L / min, denoted as 220-6-N2O. The specific preparation method is as follows:
[0068] The TC4 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A blue laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 320W and the laser beam scanning speed at 6mm / s, while the nitrogen flow rate was controlled at 20L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0069] Comparative Example 3:
[0070] Comparative Example 3 uses a TC4 substrate, a 300W blue laser, a laser beam scanning speed of 4mm / s, and a nitrogen flow rate of 20L / min, denoted as 300-4-N2O. The specific preparation method is as follows:
[0071] The TC4 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A blue laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 300W and the laser beam scanning speed at 4mm / s, while the nitrogen flow rate was controlled at 20L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0072] Comparative Example 4:
[0073] Comparative Example 4 uses a TC4 substrate, a 300W blue laser, a laser beam scanning speed of 12mm / s, and a nitrogen flow rate of 20L / min, denoted as 300-12-N2O. The specific preparation method is as follows:
[0074] The TC4 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A blue laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 300W and the laser beam scanning speed at 12mm / s, while the nitrogen flow rate was controlled at 20L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0075] Comparative Example 5:
[0076] Comparative Example 5 uses a TC4 substrate, a 300W blue laser, a laser beam scanning speed of 6mm / s, and a nitrogen flow rate of 10L / min, denoted as 300-6-N10. The specific preparation method is as follows:
[0077] The TC4 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A blue laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 300W and the laser beam scanning speed at 6mm / s, while the nitrogen flow rate was controlled at 10L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0078] Comparative Example 6:
[0079] Comparative Example 6 uses a TC4 substrate, a 300W blue laser, a laser beam scanning speed of 6mm / s, and a nitrogen flow rate of 30L / min, denoted as 300-6-N30. The specific preparation method is as follows:
[0080] The TC4 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A blue laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 300W and the laser beam scanning speed at 6mm / s, while the nitrogen flow rate was controlled at 30L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0081] Comparative Example 7:
[0082] Comparative Example 7 uses a TC4 substrate, a 300W red laser with a scanning speed of 6mm / s, and a nitrogen flow rate of 20L / min, denoted as R-300-6-N2O. The specific preparation method is as follows:
[0083] The TC4 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A red laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 300W and the laser beam scanning speed at 6mm / s, while the nitrogen flow rate was controlled at 20L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0084] Comparative Example 8:
[0085] Comparative Example 8 uses a TC4 substrate, a 250W red laser with a scanning speed of 6mm / s, and a nitrogen flow rate of 20L / min, denoted as R-250-6-N2O. The specific preparation method is as follows:
[0086] The TC4 surface was polished to a mirror finish with sandpaper, cleaned, and then placed in a laser device for in-situ nitriding. A red laser was selected and in-situ nitriding was performed in an atmospheric environment. The laser power was controlled at 250W and the laser beam scanning speed at 6mm / s, while the nitrogen flow rate was controlled at 20L / min. After the laser beam scanning was completed, the sample was cooled to room temperature and then removed for relevant characterization tests.
[0087] The following characterization was performed on the 300-6-N20, TA2-300-6-N20, TB6-300-6-N20, 250-6-N20, 300-8-N20, 300-10-N20, 300-6-N15, 300-6-N25, 220-6-N20, 320-6-N20, 300-4-N20, 300-12-N20, 300-6-N10, 300-6-N30, R-300-6-N20, and R-250-6-N20 samples prepared in Examples 1, 2, 3, 4, 5, 6, 7, and 8 and Comparative Examples 1, 2, 3, 4, 5, 6, 7, and 8: The surface macromorphology of the nitrided samples was observed, as follows: Figures 1-3 As shown, Figure 1 The macroscopic morphology observation results of Examples 1 and 4 and Comparative Examples 1 and 2 are shown in (a) for Comparative Example 1, (b) for Example 4, (c) for Example 1, and (d) for Comparative Example 2. The results show that the coating prepared by in-situ blue laser nitriding of titanium alloy has good surface morphology in the range of laser power of 250-300W. When the laser power is higher than 300W, the surface shows excessive melting; when the laser power is lower than 250W, the surface does not have obvious golden yellow color and the nitriding effect is not good. Figure 2 The macroscopic morphology observation results of Examples 1, 5, 6 and Comparative Example 3 are shown in (a) for Comparative Example 3, (b) for Example 1, (c) for Example 5, and (d) for Example 6. The results show that the coating prepared by in-situ nitriding of titanium alloy with blue laser has good surface morphology in the range of laser beam scanning speed of 6 to 10 mm / s. When the laser beam scanning speed is lower than 6 mm / s, the surface shows excessive melting. Figure 3The macroscopic morphology observation results for Examples 1, 7, 8 and Comparative Examples 5, 6 are shown below. (a) shows the macroscopic morphology of Comparative Example 5, (b) shows the macroscopic morphology of Example 7, (c) shows the macroscopic morphology of Example 1, (d) shows the macroscopic morphology of Example 8, and (e) shows the macroscopic morphology of Comparative Example 6. The results show that the coating prepared by in-situ blue laser nitriding of titanium alloy has good surface morphology within the range of high-purity nitrogen flow rate of 15-25 L / min. When the high-purity nitrogen flow rate is lower than 15 L / min, the surface does not have an obvious golden yellow color, and the nitriding effect is poor. When the high-purity nitrogen flow rate is higher than 25 L / min, the surface shows excessive melting. The macroscopic morphology observation results indicate that reasonable control of the process parameters of the nitriding process can obtain a good nitrided surface.
[0088] The microhardness distribution of the nitride layer was tested using an HV-1000 microhardness tester, such as... Figures 4-8 As shown, Figure 4 The results are the Vickers hardness test results for the cross sections of Examples 1, 2, and 3. The results show that within the effective hardened layer, Example 1 (352.4–685.1 HV) 0.05 Example 2 (339.7~632.0HV) 0.05 Example 3 (384.0~609.8HV) 0.05 The hardness of the coatings prepared by in-situ blue laser nitriding of titanium alloys was significantly improved, indicating that the hardness of the effective hardened layer increased within the range of common titanium alloys such as TC4, TA2, and TB6 as the base titanium alloy. Figure 5 The results of the Vickers hardness tests on the cross sections of Examples 1, 4, and Comparative Example 1 show that within the effective hardened layer, Example 1 (352.4–685.1 HV) 0.05 Example 4 (330.7~594.1HV) 0.05 Comparison Example 1 (277.7~320.5HV) 0.05 The higher hardness indicates that the effective hardened layer of the coating prepared by in-situ blue laser nitriding of titanium alloy increases within the laser power range of 250-300W. Figure 6 The results show the Vickers hardness test results for the cross sections of Examples 1, 5, 6 and Comparative Example 4. The results show that Example 1 (352.4~685.1 HV) 0.05 Example 5 (319.7~570.9HV) 0.05 Example 6 (284.2~429.0HV) 0.05 Comparison ratio 4 (285.3~341.7HV) 0.05 The higher hardness indicates that the effective hardened layer of the coating prepared by in-situ blue laser nitriding of titanium alloy increases within the laser beam scanning speed range of 6-10 mm / s. Figure 7The results of the Vickers hardness tests on the cross sections of Examples 1, 7, 8 and Comparative Example 5 are shown. The results show that Example 1 (352.4~685.1 HV) 0.05 Comparison ratio 7 (356.6~743.6HV) 0.05 Example 8 (313.2~545.0HV) 0.05 Comparison ratio 5 (273.2–332.9 HV) 0.05 The higher hardness indicates that the effective hardened layer of the coating prepared by in-situ nitriding of titanium alloy with blue laser increases within the range of high-purity nitrogen flow rate of 15-25 L / min. Figure 8 The results of the Vickers hardness tests on the cross sections of Examples 1 and 4 and Comparative Examples 7 and 8 are shown. The results show that Example 1 (352.4~685.1 HV) 0.05 Comparison ratio 7 (294.3~378.17HV) 0.05 Example 4 (330.7~594.1HV) 0.05 Comparison ratio 8 (269.6~321.3HV) 0.05 It has higher hardness; indicating that compared with red laser, when using blue laser, the effective hardness of the coating prepared by in-situ nitriding of titanium alloy with blue laser increases; the microhardness results may be due to the high-purity nitrogen gas being decomposed into nitrogen atoms under the high energy of the laser beam, and then participating in the reaction in the Ti molten pool to generate TiN reinforced phase, thus resulting in higher surface hardness.
[0089] The thickness of the infiltrated layer was tested using a ZEISS metallographic microscope, such as... Figures 9-13 As shown, Figure 9 The results show the cross-sectional microstructure of Examples 1, 2, and 3. (a) shows the thickness of the infiltrated layer in Example 1 (16.21 μm), (b) shows the thickness of the infiltrated layer in Example 2 (15.06 μm), and (c) shows the thickness of the infiltrated layer in Example 3 (14.58 μm). The results show that Examples 1, 2, and 3 all have good infiltrated layer thickness, indicating that within the range of common titanium alloys such as TC4, TA2, and TB6 as the substrate titanium alloy, the in-situ nitriding of titanium alloys with blue laser is more conducive to the diffusion of nitrogen atoms, forming a thicker and more uniform infiltrated layer. Figure 10 The cross-sectional microstructure results of Examples 1, 4 and Comparative Example 1 are shown. (a) shows the thickness of the infiltrated layer in Example 1 (16.21 μm), (b) shows the thickness of the infiltrated layer in Example 4 (13.46 μm), and (c) shows the thickness of the infiltrated layer in Comparative Example 1 (6.91 μm). The results show that Examples 1 and 4 have thicker infiltrated layers than Comparative Example 1. The results indicate that in the range of laser power of 250 to 300 W, in-situ nitriding of titanium alloy with blue laser is more conducive to the diffusion of nitrogen atoms and forms a thicker and more uniform infiltrated layer. Figure 11The cross-sectional microstructure results of Examples 1, 5, 6 and Comparative Example 4 are shown. (a) is the thickness of the infiltrated layer in Example 1 (16.21 μm), (b) is the thickness of the infiltrated layer in Example 5 (9.08 μm), (c) is the thickness of the infiltrated layer in Example 6 (7.31 μm), and (d) is the thickness of the infiltrated layer in Comparative Example 4 (1.55 μm). The results show that Examples 1, 5, and 6 have thicker infiltrated layers than Comparative Example 4. The results indicate that in the range of laser beam scanning speed of 6 to 10 mm / s, in-situ nitriding of titanium alloy with blue light is more conducive to the diffusion of nitrogen atoms and forms a thicker and more uniform infiltrated layer. Figure 12 The cross-sectional microstructure results of Examples 1, 7, 8 and Comparative Example 5 are shown. (a) is the thickness of the infiltrated layer in Example 8 (18.96 μm), (b) is the thickness of the infiltrated layer in Example 1 (16.21 μm), (c) is the thickness of the infiltrated layer in Example 7 (12.45 μm), and (d) is the thickness of the infiltrated layer in Comparative Example 5 (3.14 μm). The results show that Examples 1, 7, and 8 have thicker infiltrated layers than Comparative Example 5. The results indicate that in the range of high-purity nitrogen flow rate of 15-25 L / min, the in-situ nitriding of titanium alloy with blue laser is more conducive to the diffusion of nitrogen atoms and forms a thicker and more uniform infiltrated layer. Figure 13 The cross-sectional microstructure results for Examples 1, 4 and Comparative Examples 7, 8 are shown. (a) shows the thickness of the infiltrated layer in Example 1 (16.21 μm), (b) shows the thickness of the infiltrated layer in Comparative Example 7 (8.16 μm), (c) shows the thickness of the infiltrated layer in Example 4 (13.46 μm), and (d) shows the thickness of the infiltrated layer in Comparative Example 8 (6.49 μm). The results show that Example 1 has a thicker infiltrated layer than Comparative Example 7, and Example 4 has a thicker infiltrated layer than Comparative Example 8. The results indicate that compared with red lasers, when using blue lasers, the in-situ nitriding of titanium alloys with blue lasers is more conducive to the diffusion of nitrogen atoms, forming a thicker and more uniform infiltrated layer. The microstructure results show that the in-situ nitriding technology with blue lasers provides sufficient conditions for the diffusion of nitrogen atoms, promoting the diffusion of nitrogen into the interior of the molten pool.
[0090] Nanoindentation testing is used to evaluate the mechanical properties of sample surfaces, such as... Figures 14-18 As shown, Figure 14 The surface hardness results for Examples 1, 2, and 3 show that Examples 1 (8.59±0.44GPa), 2 (7.71±0.73GPa), and 3 (8.22±0.74GPa) have higher surface hardness compared to the untreated sample. This indicates that within the range of common titanium alloys such as TC4, TA2, and TB6 as the substrate titanium alloy, the coating prepared by blue laser in-situ nitriding of titanium alloys has higher surface hardness. Figure 15The surface hardness results for Examples 1, 4 and Comparative Example 1 show that Examples 1 (8.59±0.44GPa) and 4 (7.27±0.56GPa) have higher surface hardness than Comparative Example 1 (3.29±0.095GPa), indicating that in the range of laser power of 250-300W, the coating prepared by in-situ blue laser nitriding of titanium alloy has higher surface hardness. Figure 16 The surface hardness results for Examples 1, 5, 6 and Comparative Example 4 show that Examples 1 (8.59±0.44GPa), 5 (6.96±0.26GPa), and 6 (5±0.24GPa) have higher surface hardness (approximately 1.5 to 3.5GPa higher) than Comparative Example 4 (3.55±0.274GPa). This indicates that in the range of laser beam scanning speed of 6 to 10 mm / s, the coating prepared by in-situ blue laser nitriding of titanium alloy has higher surface hardness. Figure 17 The surface hardness results for Examples 1, 7, 8 and Comparative Example 5 show that Examples 1 (8.59±0.44GPa), 7 (4.99±0.21GPa), and 8 (9.07±0.58GPa) have higher surface hardness than Comparative Example 5 (3.16±0.16GPa). The results indicate that the coating prepared by in-situ blue laser nitriding of titanium alloy has higher surface hardness within the range of high-purity nitrogen flow rate of 15-25 L / min. Figure 18 The surface hardness results for Examples 1 and 4 and Comparative Examples 7 and 8 show that Example 1 (8.59 ± 0.44 GPa) has a higher surface hardness than Comparative Example 7 (4.32 ± 0.16 GPa), Example 4 (7.27 ± 0.56 GPa), and Comparative Example 8 (3.46 ± 0.27 GPa). These results indicate that, compared to a red laser, the in-situ nitriding of titanium alloys using a blue laser results in higher surface hardness. The nanoindentation results suggest that the high-purity nitrogen gas is decomposed into nitrogen atoms under the high energy of the laser beam, subsequently reacting in the Ti molten pool to generate a TiN-reinforced phase, thus resulting in higher surface hardness.
[0091] XRD analysis of sample surface phase composition, such as Figure 19 As shown, the results indicate that TiN diffraction peaks were detected in Examples 1 and 5, and Ti2N diffraction peaks were detected in Example 6. No TiN or Ti2N diffraction peaks were detected in Comparative Example 4. This shows that the coating preparation by in-situ blue laser nitriding of titanium alloy was successful within the range of 6 to 10 mm / s of laser beam scanning speed.
[0092] The above description is merely a preferred embodiment of the present invention and is illustrative rather than restrictive. Those skilled in the art will understand that many changes, modifications, and even equivalents can be made within the spirit and scope defined by the claims of the present invention, all of which will fall within the protection scope of the present invention.
Claims
1. A method for preparing a coating by in-situ blue laser nitriding of titanium alloys, characterized in that, Includes the following steps: S1, Substrate pretreatment: Polish the titanium alloy substrate surface to a mirror finish with sandpaper, and clean it with alcohol and pure water for later use. S2, Laser in-situ nitriding: The titanium alloy matrix obtained in step S1 is placed in a laser device, a laser is selected, and high-purity nitrogen gas is delivered through the coaxial protector nozzle of the processing head. At the same time, the laser power and laser beam scanning speed are adjusted to perform laser in-situ nitriding treatment.
2. The method for preparing a coating by in-situ blue laser nitriding of titanium alloy as described in claim 1, characterized in that, The base titanium alloy in step S1 is one of TC4, TA2 and TB6.
3. The method for preparing a coating by in-situ blue laser nitriding of titanium alloy as described in claim 1, characterized in that, The laser power in step S2 is 250-300 W.
4. The method for preparing a coating by in-situ blue laser nitriding of titanium alloy as described in claim 1, characterized in that, The scanning speed of the laser beam in step S2 is 6 to 10 mm / s.
5. The method for preparing a coating by in-situ blue laser nitriding of titanium alloy as described in claim 1, characterized in that, The flow rate of high-purity nitrogen in step S2 is 15-25 L / min.
6. The method for preparing a coating by in-situ blue laser nitriding of titanium alloy as described in claim 1, characterized in that, The laser in step S2 is a blue laser.
7. The method for preparing a coating by in-situ blue laser nitriding of titanium alloy as described in claim 1, characterized in that, The working environment in step S2 is an atmospheric environment.
8. A coating prepared by laser in-situ nitriding of titanium alloy as described in any one of claims 1 to 7.
9. The application of the coating as described in claim 8 in the fields of aerospace, marine engineering and biomedicine.